THE ROLE OF FINTECH IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Abdul Manap; Rini Yulia Sasmiyati; Norman Edy; Nurhaifa Idris; Saut Pan (SEAN Institute, 2023)
Financial technology (Fintech) is a combination of technology with financial/financial services which eventually develops towards a business model from conventional to online, which initially pays face-to-face and carries a certain amount of cash, can now make remote transactions by making payments that can be done in seconds. This study discusses the role of Fintech in Micro, Small and Medium Enterprises. The case studies in this study are SMEs in Pekalongan, Batang and Pemalang districts. The role of Fintech when viewed from financial literacy and financial inclusion in MSMEs. From the results of the analysis that Fintech developments carried out by financial institutions, be it banking, savings and loan cooperatives and other finance can increase financial literacy and financial inclusion in MSMEs.